There Is No Simple Model of the Plasma Membrane Organization - Bernardino de la Serna, Jorge; Schütz, Gerhard J.; Eggeling, Christian; Cebecauer, Marek (Frontiers in Cell and Developmental Biology, 2016)
Ever since technologies enabled the characterisation of eukaryotic plasma membranes, heterogeneities in the distributions of its constituents were observed. Over the years this led to the proposal of various models describing the plasma membrane organisation such as lipid shells, picket-and-fences, lipid rafts, or protein islands, as addressed in numerous publications and reviews. Instead of emphasising on one model we in this review give a brief overview over current models and highlight how current experimental work in one or the other way do not support the existence of a single overarching model. Instead, we highlight the vast variety of membrane properties and components, their influences and impacts. We believe that highlighting such controversial discoveries will stimulate unbiased research on plasma membrane organisation and functionality, leading to a better understanding of this essential cellular structure.